Design Education, Mobile Photography and Its Propagation in Social Media: Photography Workshop for Kargil Students - Keyur S. Sahasrabudhe, Pranita Ranade (International Journal of Modern Agriculture, 2020)
This research deals with the experience to work and know the understanding of undergraduate students of Kargil in the domain of mobile photography. Three hours of photography workshop on mobile photography conducted for Kargil students. The focus of this workshop was to impart knowledge of photography using a mobile camera and its operations with the basic principles of photography with the latest technology e.g. photograph sharing, editing software. Students’ performance is assessed by pre and post-test. It was a challenging task to conduct the insightful workshop in stipulated time and share the feedback. Andragogy workshop content is developed based upon the ‘Perception-in-Action’ model (Schön). The aim of the workshop is not only to enhance the knowledge about the mobile camera, photography and technology among the students but it will help to promote the tourism industry of Kargil sector by posting photographs on social media. By regular practice and experiential learning of photographic skills, these amateur photographer’s skills will enhance and they can earn by selling their photographs online on various websites. It eventually helps them in generating the employability. The objective of the workshop is to understand, identify strategies to develop students’ perception in design education.